Chimeric antigen receptor T-cell therapy in acute myeloid leukemia. Issue 2 (March 2022) - Koedam, Jan; Wermke, Martin; Ehninger, Armin; Cartellieri, Marc; Ehninger, Gerhard
Abstract : Purpose of review: Treatment outcome of relapsed or refractory AML patients remains dismal and new treatment options are needed. Adoptive cell therapy using CAR-T cells is a potentially interesting approach in this. Recent findings: Several potentially interesting AML targets are being investigated with CAR-T therapy with over 60 clinical trials listed on clinicaltrials.gov. The first clinical data are only just emerging with mixed results, once more proving that further research is needed. Summary: Adoptive cell therapy using chimeric antigen receptor T cells is being investigated in AML through many clinical trials. So far, no AML-specific antigen has been identified, requiring additional strategies to mitigate on-target off-tumor toxicity and to increase efficacy. Focus point is to acquire control over the CAR T cells once administered. Strategies to do so include biodegradable CARs, inducible CARs, suicide-switch containing CARs and two-component modular CARs. Limited and mixed results are available, confirming the risk of lasting toxicity for nonswitchable CARs. Initial results of modular CARs suggest toxicity can be mitigated whilst maintaining CAR activity by the use of modular CAR concepts that allows for 'ON' and 'OFF' switching. Abstract : Supplemental Digital Content is available in the text